Action of Proline on Stomata Differs from That of Abscisic Acid, G-Substances, or Methyl Jasmonate - Raghavendra, A. S. (1987)
Methyl jasmonate (MJ) and a mixture of G(1), G(2), and G(3) (G-substances) inhibited stomatal opening in abaxial epidermis of Commelina benghalensis and complete closure occurred at 10(−6) molar MJ, or 10(−3) molar G-substances compared to 10(−5) molar abscisic acid (ABA). Proline, even at 10(−3) molar caused only a partial stomatal closure. Apart from ABA, other endogenous plant growth regulators do regulate stomata. Reduction in the stimulation by fusicoccin and complete stomatal closure, at 30 millimolar KCl or less, were affected by ABA, MJ, or G-substances, but not by proline. The action of MJ or G-substances was similar to ABA in decreasing proton efflux and the levels of potassium, malate, or reducing sugars. Proline, however, interfered with starch-sugar interconversion but had no effect on proton efflux or potassium content of epidermis.